INTEGRATING TECHNOLOGY IN THE ASSESSMENT AND EGG SORTING SYSTEM OF FARM EGG QUALITY - Concha-Ajado, Berna Joy Queenie (Journal for Technology and Science, 2026)
Objective: This research assessed the acceptability of the developed sensor based for the assessment and inventory tracking system of farm egg quality during the academic year 2024-2025 towards technology adoption. Craft and implement the proposed system design of farm egg quality and tracking system. Method: This research study employed quantitative research using applied design with the use of descriptive methods to assess the acceptability of the develop sensor-based inventory tracking system of farm egg quality. Experts and non-experts from the Computer Technology and Agriculture Departments at Cebu Technological University-Tuburan Campus, as well as owners of poultry farms, made up the respondents. Results: With an overall factor average mean of 4.51 HA, the system was regularly rated better by non-experts (4.57) than by experts (4.44). Although the system is highly appreciated, real-world application still confronts modest obstacles, as seen by the maximum score of 4.73 HA for perceived usefulness and the lowest score of 4.29 HA for actual utilization. Perceived usability, use with behavioral goals, and actual usage were all strongly positively correlated. Its capacity to improve efficiency, expedite processes, and track egg quality in real time was especially appreciated by users. Concerns were expressed regarding the system's automated efficiency, tracking of financial data, and integration with current farm management technologies. The obvious relationship between usability, users' intentions, and actual usage highlights the necessity of a straightforward and user-friendly design to encourage adoption. Novelty: Its capacity to improve efficiency, expedite processes, and track egg quality in real time was especially appreciated by users.